Green House Gas Control and Agricultural Biomass for Sustainable Animal Agriculture in Developing Countries - Takahashi, J (Indonesian Bulletin of Animal and Veterinary Sciences, 2010)
Important green house gases (GHG) attributed to animal agriculture are methane (CH4) and nitrous oxide (N2O), though carbon dioxide (CO2) contributes almost half of total greenhouse effect. Rumen CH4 production in an enteric fermentation can be accounted as the biggest anthropogenic source. Some of prebiotics and probiotics have been innovated to mitigate rumen CH4 emission. The possible use of agricultural biomass consisted of non-edible parts of crop plants such as cellulose and hemi cellulose and animal wastes was proposed as a renewable energy and nitrogen sources. The ammonia stripping from digested slurry of animal manure in biogas plant applied three options of nitrogen recycling to mitigate nitrous oxide emission. In the first option of the ammonia stripping, the effect of ammonolysis on feed value of cellulose biomass was evaluated on digestibility, energy metabolism and protein utilization. Saccharification of the NH3 treated cellulose biomass was confirmed in strictly anaerobic incubation with rumen cellulolytic bacteria, Ruminoccous flavefaciens, to produce bio-ethanol as the second option of ammonia stripping. In an attempt of NH3 fuel cell, the reformed hydrogen from the NH3 stripped from 20 liter of digested slurry in thermophilic biogas plant could generate 0.12 W electricity with proton exchange membrane fuel cell (PEM) as the third option. Key words: GHG, rumen, methane, probiotics, ammonia stripping, biomass